TOPONYMS IN PROVERBS - Mikhail Bredis; Olga Lomakina (Proverbium, 2019)
This article provides a comparison between Russian, Latvian, Lithuanian, Polish, German, French, English, Finnish, and Tajik proverbs with toponyms. It deals with groups of proverbs notable for their semantics: toponyms as symbols and measure of significance and a long, rich history; toponyms as a symbol of an objective, a destination point; toponyms and their characteristics in relation to wealth and money. A generalised imageless proverbial idea is used for comparison.